COVID-19 cases treated with classical homeopathy: a retrospective analysis of International Academy of Classical Homeopathy database - Seema Mahesh; Petr Hoffmann; Cristiane Kajimura; George Vithoulkas; International Academy of Classical Homeopathy (IACH) COVID Collaborators (Journal of Global Health Reports)
# Background